Effect of melatonin on oxidative stress markers in patients with alopecia areata - AL- Gaff AN; Humadi S; Wohaieb S.A (University of Mosul, 2005)
Alopecia areata is an autoimmune, nonscarring, multifocal disorder of hair growth characterized by circular bald areas, which occur on any hair bearing site of the body. The exact cause of alopecia areata is unknown. Recent study reported a potential role of oxygen free radicals (OFR) in pathogenesis of alopecia areata. This clinical study was designed to evaluate the antioxidant effect of melatonin (3 mg every other day ) in patients with alopecia areata. This study revealed that two month treatment with melatonin antioxidant led to a decrease in the basal level of malondialdehyde (MDA) an index of lipid peroxidation, an increase in basal glutathione (GSH) content a major endogenous antioxidant in both plasma and erythrocytes and an increase in plasma total antioxidant status( TAS ) . The most important point is the clinical significance of antioxidants in improving the hair growth response of patients with alopecia areata. This may be due to direct and/or indirect effect of melatonin on immune system. The direct effect may be through its immunoenhancing / immunostimulatory properties of melatonin.The indirect effect is the scavenging activity of this antioxidant, which in turn decrease damaging effect of oxygen free radicals (OFR) and utilization of GSH in neutralizing phagocytes- induced free radicals. So replenishment of GSH within natural killer (immune) cells strengthens the immune system and increases the rate of hair growth.